THE MEANING OF ADVICE SIGNS IN DIWAN ALI BIN ABI THALIB THE STUDY OF PRAGMATIC SEMIOTICS - Sukardi Sukardi; Muhammad Dedad Bisaraguna Akastangga; Zainul Zainul (LLDIKTI Wilayah X, 2022)
Diwan Ali Bin Abi Talib is a literary work that is poetic and rich in the meaning of worldly advice. To reveal the poetic meaning of worldly advice in Ali Bin Abi Talib's verse, a deeper study is needed in terms of form and content. This study examines worldly advice in the diwan of Ali Bin Abi Talib. The purpose of this study is to reveal the meaning of the sign and the purpose of the speech of advice in Ali Bin Abi Talib's diwan specifically. The method used in this research is descriptive qualitative with semiotic and pragmatic approaches. Semiotics is used to describe the meaning of signs in the stanzas of advice poetry. While pragmatics is used to describe the purpose of the advice utterance. The results of this study indicate that there are 334 verses that can be used as guidelines for life in the diwan Ali Bin Abi Talib. Semiotically, the signs are found in the form of phrases, clauses, and sentences, each of which is spread out in each stanza. The signs form the whole meaning unified. Pragmatically,the meaning of the utterances is found.